Dp71Δ78‐79 dystrophin mutant stimulates neurite outgrowth in PC12 cells via upregulation and phosphorylation of HspB1. Issue 9 (13th April 2016) - Merino‐Jiménez, Candelaria; Aragón, Jorge; Ceja, Víctor; Rodríguez‐Martínez, Griselda; Cázares‐Raga, Febe E.; Chardonnet, Solenne; Pionneau, Cédric; Rendon, Alvaro; Montañez, Cecilia
Abstract : PC12 cells acquire a neuronal phenotype in response to nerve growth factor (NGF). However, this phenotype is more efficiently achieved when the Dp71Δ78‐79 dystrophin mutant is stably expressed in PC12‐C11 cells. To investigate the effect of Dp71Δ78‐79 overexpression on the protein profile of PC12‐C11 cells, we compared the expression profiles of undifferentiated and NGF‐differentiated PC12‐C11 and PC12 cells by 2DE. In undifferentiated cultures, one protein was downregulated, and five were upregulated. Dp71Δ78‐79 overexpression had a greater effect on differentiated cultures, with ten proteins downregulated and seven upregulated. The protein with the highest upregulation was HspB1. Changes in HspB1 expression were validated by Western blot and immunofluorescence analyses. Interestingly, the neurite outgrowth in PC12‐C11 cells was affected by a polyclonal antibody against HspB1, and the level of HspB1 and HspB1Ser86 decreased, suggesting an important role for this protein in this cellular process. Our results show that Dp71Δ78‐79 affects the expression level of some proteins and that the stimulated neurite outgrowth produced by this mutant is mainly through upregulation and phosphorylation of HspB1.